2015
DOI: 10.1007/s11999-015-4375-x
|View full text |Cite
|
Sign up to set email alerts
|

Do Upper Extremity Trauma Patients Have Different Preferences for Shared Decision-making Than Patients With Nontraumatic Conditions?

Abstract: Background Shared decision-making is a combination of expertise, available scientific evidence, and the preferences of the patient and surgeon. Some surgeons contend that patients are less capable of participating in decisions about traumatic conditions than nontraumatic conditions. Questions/purposes (1) Do patients with nontraumatic conditions have different preferences for shared decisionmaking when compared with those who sustained acute trauma? (2) Do disability, symptoms of depression, and self-efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Providing patients with their desired level of involvement in decision-making is an important part of improving patient engagement and clinical results [24], and future studies are required to determine whether meeting patients' preferences actually results in better outcomes in CTS. In this regard, decision aids that are appropriate for patients with limited health literacy might help them achieve their preferred role in decision-making [16,19,23]. A physician should consider informing and recommending treatment programs for CTS with concise explanations tailored to basic levels of health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…Providing patients with their desired level of involvement in decision-making is an important part of improving patient engagement and clinical results [24], and future studies are required to determine whether meeting patients' preferences actually results in better outcomes in CTS. In this regard, decision aids that are appropriate for patients with limited health literacy might help them achieve their preferred role in decision-making [16,19,23]. A physician should consider informing and recommending treatment programs for CTS with concise explanations tailored to basic levels of health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that most patients preferred an active or active‐shared role, wherein they assume more control over the decision than the provider, differs from that of prior studies using the Control Preferences Scale in nonmental health samples. Studies in patients with breast cancer (Janz et al., ), traumatic injury (Hageman et al., ), and in a pooled analysis of more than 3,000 cancer patients (Singh et al., ) reported that a collaborative approach, in which the patient and provider equally share decisional control, was most preferred. It is possible that characteristic features of PTSD, including mistrust of providers or a desire to be in control of situations, may have resulted in an increased desire for decisional control.…”
Section: Discussionmentioning
confidence: 99%
“…The CPS is easily administered, is valid in health-care decision making, 14 and has been used across varying disease types. [15][16][17][18] In addition, it has been adapted for selfadministration without the need for detailed instructions 19 using a 5-point visual scale (Figure 1). Research using the CPS in MS has shown high levels of autonomy in decision making and role preference variations with age, sex, and disease course.…”
mentioning
confidence: 99%